2015
DOI: 10.4103/0253-7613.169577
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of rosiglitazone, quercetin, and their combination on fructose-induced metabolic syndrome in rats

Abstract: Objectives:Quercetin exhibits a wide range of biological functions. The present study aimed to investigate the possible beneficial effects of rosiglitazone, quercetin as well as their combination on metabolic and biochemical changes associated with the fructose-induced metabolic syndrome (MS).Materials and Methods:Four groups of rats were fed on fructose-enriched diet for 14 weeks. One group served as fructose-enriched diet control, while the remaining groups were treated with rosiglitazone (4 mg/kg/day), quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…These studies indicated that quercetin seems to be more effective in antidiabetes than antiobesity. A similar result was found in quercetin‐fed male Wistar rats with the consumption of a high‐fructose diet, which was shown as a lowered plasma insulin and HOMA‐IR index . The quercetin (50 mg/kg body weight) treatment for 4 wk not only restored the high‐fructose diet‐caused reduction in adiponectin but also TNF‐α in epididymal adipose tissue of rats.…”
Section: Chemoprevention Potential Of Dietary Natural Compounds: Targsupporting
confidence: 75%
“…These studies indicated that quercetin seems to be more effective in antidiabetes than antiobesity. A similar result was found in quercetin‐fed male Wistar rats with the consumption of a high‐fructose diet, which was shown as a lowered plasma insulin and HOMA‐IR index . The quercetin (50 mg/kg body weight) treatment for 4 wk not only restored the high‐fructose diet‐caused reduction in adiponectin but also TNF‐α in epididymal adipose tissue of rats.…”
Section: Chemoprevention Potential Of Dietary Natural Compounds: Targsupporting
confidence: 75%
“…Several studies showed that high fat and high fructose diets induce insulin resistance and tissue damage. Excess fructose diet increases the lipid synthesis and metabolic diseases which cause lipotoxic cellular dysfunction and cause accumulation of lipids induces damages in the liver and kidney (Abo-youssef 2015 ; Hao et al 2015 ; De Castro et al 2013 ). The histology of kidney stained with H & E. Group 1 shows the normal architecture of the kidney (Plate 1).…”
Section: Resultsmentioning
confidence: 99%
“…Insulin levels were measured using rat insulin enzyme-linked immunosorbent assay kit (Mercodia, Uppsala, Sweden) in serum. 11 …”
Section: Methodsmentioning
confidence: 99%